2014
DOI: 10.1007/s13105-014-0345-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α-induced nuclear factor-kappaB activation in human cardiomyocytes is mediated by NADPH oxidase

Abstract: An elevated level of tumor necrosis factor (TNF)-α is implicated in several cardiovascular diseases including heart failure. Numerous reports have demonstrated that TNF-α activates nuclear factor (NF)-kappaB, resulting in the upregulation of several genes that regulate inflammation, proliferation, and apoptosis of cardiomyocytes. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, a major source of reactive oxygen species (ROS), is also activated by TNF-α and plays a crucial role in redox-sensitive si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 51 publications
2
30
0
Order By: Relevance
“…105 These phenomena are mediated by activation of p38MAPK and NF-κB 106 in a ROS-dependent manner. 105,[107][108][109] In line with these findings, in vivo studies demonstrated a hypertrophic response in cardiac myocytes, leading to left ventricular hypertrophy and dilatation upon cardiac-specific overexpression or chronic infusion of high doses of TNF-α. 94,105,110 Cardiac myocytes have further been shown to undergo apoptosis after stimulation with TNF-α in vitro.…”
Section: Role In Cardiac Myocytessupporting
confidence: 53%
“…105 These phenomena are mediated by activation of p38MAPK and NF-κB 106 in a ROS-dependent manner. 105,[107][108][109] In line with these findings, in vivo studies demonstrated a hypertrophic response in cardiac myocytes, leading to left ventricular hypertrophy and dilatation upon cardiac-specific overexpression or chronic infusion of high doses of TNF-α. 94,105,110 Cardiac myocytes have further been shown to undergo apoptosis after stimulation with TNF-α in vitro.…”
Section: Role In Cardiac Myocytessupporting
confidence: 53%
“…TNF-α is a pro-inflammatory cytokine that is closely related to the physiopathology of several cardiovascular diseases through the upregulation of genes that control inflammation, proliferation and apoptosis in cardiomyocytes [75]. Previous works have shown that other adipokines can modulate the effect of TNF-α, particularly the adipokine leptin, a crucial regulator of energy homeostasis that confers protection against the apoptosis induced by TNF-α [45].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Tumor cell growth and invasion are regulated by a network of factors, among which nuclear factor κB (NF-κB) is a critical one that regulates the expression of various genes involved in immunity, stress responses, inflammation and the inhibition of apoptosis, thus providing appropriate conditions for tumor cell progression [22][23][24]. NF-κB is constitutively activated in some tumor cells, including HCC cells, and contributes to the maintenance of the highly proliferative malignant phenotype as well as cellular invasion [22][23][24].…”
Section: Introductionmentioning
confidence: 99%